1998
DOI: 10.1046/j.1469-8137.1998.00305.x
|View full text |Cite
|
Sign up to set email alerts
|

Persistent, non‐seed‐size maternal effects on life‐history traits in the progeny generation in squash, Cucurbita pepo

Abstract: Maternal-environmental effects on subsequent progeny life-history traits were evaluated in squash (Cucurbita pepo L.) in terms of the amount of time available for seed development, and the timing of fruit production. Progeny arising from three kinds of fruit were compared. Plants from which fruits were removed 3 d post-pollination throughout the growing season developed only ' late ' fruits (during 10-15 d) at the end of the growing season ; on control plants both ' early ' and ' late ' fruits developed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 56 publications
0
13
0
Order By: Relevance
“…Maternal effects are widely recognized as having important effects on offspring performance (reviewed by Roach & Wulff, 1987; Donohue & Schmitt, 1998, but see Weinig, 2000). Their effects may carry through to later stages of the offspring's life (El‐Keblawy & Lovett‐Doust, 1998) and even persist across generations (Wulff et al. , 1999, but see Andalo et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Maternal effects are widely recognized as having important effects on offspring performance (reviewed by Roach & Wulff, 1987; Donohue & Schmitt, 1998, but see Weinig, 2000). Their effects may carry through to later stages of the offspring's life (El‐Keblawy & Lovett‐Doust, 1998) and even persist across generations (Wulff et al. , 1999, but see Andalo et al.…”
Section: Discussionmentioning
confidence: 99%
“…Maternal effects are widely recognized as having important effects on offspring performance (reviewed by Roach & Wulff, 1987;Donohue & Schmitt, 1998, but see Weinig, 2000). Their effects may carry through to later stages of the offspring's life (El-Keblawy & Lovett-Doust, 1998) and even persist across generations (Wulff et al, 1999, but see Andalo et al, 1999. However, significant environmental maternal effects are most commonly reported to affect early offspring traits, either because their effects on later traits are not examined (Huxman et al, 1998;Agrawal, 2002) or because their effect diminishes over the offspring's lifetime (Weiner et al, 1997;Steinger et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Our pattern of inbreeding depression, based on naturally occurring densities of seedlings, can be interpreted in the light of the dominance and suppression hypothesis (Weiner, 1985), which postulates that a small initial advantage (for instance in seed mass) is enhanced when competition occurs. Indeed, many studies have demonstrated that slight differences in seed mass may translate into high fitness differences (El-Keblawy and Lovett-Doust, 1998). In the present study, the significant difference in achene mass between inbred and outbred types may be the basis for the patterns observed.…”
Section: Discussionmentioning
confidence: 99%
“…We hypothesize that the acquisition of the physiological traits necessary to germinate and survive in the upper canopy environment, such as in the Chilean holoepiphyte S. repens , could be a consequence of maternal effects in an ancestral secondary hemiepiphytic liana, when subjected to increasing water stress in the upper canopy, especially during fertilization and seed development. As initial seedling growth depends on minerals, photosynthates and phytohormones provided by the maternal parent (Roach & Wulff, 1987; Sultan, 1996), differences in seed provisioning could affect subsequent development (Sultan, 1996) and progeny traits, such as seed size and seed germination requirements (El‐Keblawy & Lovett‐Doust, 1998; Johnsen et al ., 2005).…”
Section: Discussionmentioning
confidence: 99%